High ovarian hormones present during fear extinction reduce fear relapse through a nigrostriatal dopamine pathway - Alyssa A. Hohorst; Margaret K. Tanner; Rebecca Han; Kamryn M. Korth; Jessica D. Westerman; Carolina Sanchez Mendoza; Miles Q. Dryden; Lareina A. Alvarez; Remla A. Abdul; Esteban C. Loetz; Erik B. Oleson; Benjamin N. Greenwood (Biology of Sex Differences)
Abstract Background Elevated ovarian hormones during fear extinction can enhance fear extinction memory retention and reduce fear renewal, but the mechanisms remain unknown. High levels of ovarian hormones are associated with heightened dopamine (DA) transmission, a key player in fear extinction. In males, stimulation of substantia nigra (SN) DA neurons during fear extinction reduces renewal; an effect mimicked by DA D1 receptor agonist administration into the dorsolateral striatum (DLS), a primary target of the SN. The current studies tested the role of the SN-DLS pathway in estrous cycle-modulation of fear extinction and relapse. Methods Male and female Long-Evans rats were used to investigate the effects of sex and ovarian hormone levels during fear extinction on later fear relapse and underlying mechanisms. Fear extinction-induced cFos in SN DA neurons was quantified with double-label immunohistochemistry. An intersectional chemogenetic approach was used to determine whether SN-DLS pathway activity during fear extinction is necessary and sufficient for observed effects of ovarian hormones on fear relapse. Finally, fast scan cyclic voltammetry revealed the effects of sex and ovarian hormones on electrically-evoked DA release in the DLS and verified the effectiveness of chemogenetic approaches. Results Female rats exposed to fear extinction during proestrus or estrus (Pro/Est; high hormones) had less relapse (renewal and spontaneous recovery) compared to males or females exposed to fear extinction during metestrus or diestrus (Met/Di; low hormones). Fear extinction-induced cFos within SN DA neurons and electrically-evoked DA release in the DLS was highest in female rats during Pro/Est. The behavioral and neurochemical effects of Pro/Est were mimicked by estradiol administration to ovariectomized female rats. Inhibition of the SN-DLS pathway suppressed electrically-evoked DA release in the DLS and restored fear renewal in females exposed to simultaneous fear extinction and SN-DLS inhibition during Pro/Est. Conversely, stimulation of the SN-DLS pathway during extinction reduced fear renewal in males. Conclusions Results indicate that ovarian hormones present during fear extinction reduce later fear relapse through a SN-DLS dopamine pathway. Data suggest the SN-DLS DA pathway is a novel target for the reduction of fear relapse in both sexes.